If it's not what You are looking for type in the equation solver your own equation and let us solve it.
49-(2c+4)=4(c+6)=c
We move all terms to the left:
49-(2c+4)-(4(c+6))=0
We get rid of parentheses
-2c-(4(c+6))-4+49=0
We calculate terms in parentheses: -(4(c+6)), so:We add all the numbers together, and all the variables
4(c+6)
We multiply parentheses
4c+24
Back to the equation:
-(4c+24)
-2c-(4c+24)+45=0
We get rid of parentheses
-2c-4c-24+45=0
We add all the numbers together, and all the variables
-6c+21=0
We move all terms containing c to the left, all other terms to the right
-6c=-21
c=-21/-6
c=3+1/2
| -5=-4+r/10 | | -6x=5=41 | | 4x2-7x-4=0 | | 3(4x+8)=12x=16=8 | | 0.5y-6=-12 | | 3(2x-3)^2+17(2x-3)+10=0 | | 8x+44=76 | | 1/2(2w-1)-3=1 | | 3(2a-3)^2+17(2a-3)+10=0 | | 8=n/18+7 | | 11(5-13d=) | | 125x+132x+72x=329 | | 3x^2=5.25 | | 8+3(2y-1)=4 | | 7(u-8u)=3)(u+4) | | x-(-)3x=14-4x | | n-4=2 | | x-3x=14+-4x | | 7b+8=-7+4b | | X+2+10x=20+9x | | 3p^2-120=-9p | | 4x=6+4x | | 16(7=5b) | | m−1.47=12.15 | | 2y-10-5y=2 | | 7y-3y-7=60.48 | | 4x2+6x-4=0 | | 5y-3y-14=25.36. | | 6*x+5=81 | | 11+-11+9x=29 | | x–1=-4 | | 3x+3x-3x-2=11 |